Econometric models in the evaluation of natural attractiveness for the development of tourism in Golija - Madžović, Ilhana; Ž. Vukoičić, Danijela (Economic Outlook, 2023)
Tourism is one of the most important sectors for development in many countries. In addition to attractive tourist destinations, tourist trends are moderate towards unused, attractive areas with a high degree of preservation. The evaluation of such areas is of great importance for the planning of tourism development. Economic models are used in their study. One of those areas in Serbia is the Natural Good - Nature Park "Golija", Biosphere Reserve "Golija-Studenica". The subject of the paper's research are economic models important for the evaluation of natural attractiveness in order to develop tourism in Golija. The aim of the work is to identify and value the resources relevant for the development of tourism in the Golija area. Within the methodological apparatus, as a general scientific method, a model based on numerical and statistical analysis, cartographic, analysis, synthesis, descriptive method was used.
Keywords: Golija, tourism, econometric models